181k views
2 votes
I need help with algebra 2 work pls ASAP

I need help with algebra 2 work pls ASAP-example-1
User Thotheolh
by
4.8k points

1 Answer

4 votes

9514 1404 393

Answer:

g(x) = (x +1)^2 +3

Explanation:

You know that the transformation ...

g(x) = f(x -h) +k

moves the f(x) graph h units to the right and k units up. In this problem, we have h=-1 (1 unit left) and k=3 (3 units up), so the transformation is ...

g(x) = f(x +1) +3

Since f(x) = x^2, the equation for g(x) is ...

g(x) = (x +1)^2 +3

I need help with algebra 2 work pls ASAP-example-1
User Saber Alex
by
4.3k points